PERAN OVERLAPPING GENERATIONS MODEL DALAM MENINGKATKAN KONSUMSI KESEHATAN RUMAH TANGGA - Ariansyah, Candra; Shofwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
A decline in household consumption expenditure on health may indicate a decline in households' ability to prevent health problems and treat illnesses. The proportion of household expenditure on health consumption is very small compared to the proportion of non-health consumption. Spending on health is still not a top priority for households compared to other expenditure components. One approach to understanding intergenerational health consumption is to use the Overlapping Generations (OLG) Model. The research objective is to analyse the factors that influence health consumption with the OLG model approach. Based on the test results using FDGMM and SYSGMM analysis, the previous year's health consumption, income, savings, labour, inflation, and Government Health Insurance (JKN) affect household health consumption. Keywords: Household, OLG Model, Health Consumption, Income, Saving, Labour, Inflation, Government Health Insurance